UJI PENGARUH VARIASI SUDU TURBIN PADA SUDUT KEMIRINGAN POROS 15 DERAJAT TERHADAP DAYA DAN EFISIENSI TURBIN ARCHIMEDES - Maulana, Agung (Politeknik Harapan Bersama Tegal, 2024)
The need for electrical energy sources increases along with the increasing population in Indonesia. While the electrical energy used today is sourced from fossils that are starting to run out. So there is a need for alternative energy sources to replace fossils. One of them is by utilizing the river flow which is converted into electrical energy which is called a screw turbine power plant. This study uses an Archimedes Screw Turbine, with a tilt angle of 15 degrees, at variations of blade 1,2 and blade 3 to test the electrical power and efficiency of the turbine. The results of the 1 blade test at an angle of 15 degrees obtained electrical power of 8.17 watts and turbine efficiency of 75.92655%. The results of the 2 blade test at an angle of 15 degrees obtained an electric power of 7.16 watts and a turbine efficiency of 66.54028%. The results of the 3 blade test at an angle of 15 degrees obtained an electric power of 7.45 watts and a turbine efficiency of 69.23534%. Thus the use of blade 3 at an angle of 15 degrees produces greater electrical power and efficiency for blade 1, the result is greater than blade 2 and blade 3